E-commerce and entrepreneurship in SMEs: case of myBot. Issue 3 (18th June 2018) - Shemi, Alice P.; Procter, Chris
Abstract : Purpose: The adoption of e-commerce in small and medium enterprises (SMEs) is a much researched topic in developed and developing nations. The application of mobile devices, and social media networks (SMNs) such as Facebook has revolutionalised the e-commerce adoption process in SMEs. However, research into this area is still developing and there is a dearth of knowledge on how SMEs in developing countries enact and apply this phenomenon. The purpose of this paper is to explain how e-commerce entrepreneurship using SMN is conceptualised and applied in SMEs, and to highlight factors that influence this e-commerce innovation. Design/methodology/approach: An interpretive and qualitative case study approach was adopted as a methodological foundation in a firm pseudo-named, myBot. The study employed the contextualism theory as a meta-theoretical framework to conceptualise and analyse the e-commerce entrepreneurship process in the firm. The study employed face-to-face semi-structured and unstructured interviews with the manager as primary means of obtaining in-depth information. Further information was obtained through website content analysis and document analysis of the firm's reports and observations. Findings: The results unearth a socially constructed feature of e-commerce entrepreneurship that draws from myBot's manager's innovative ability to use Facebook and e-mail to increase sales through its niche market. Factors that propelled e-commerce entrepreneurial activities using Facebook include trust, commitment and innovativeness. Research limitations/implications: The revelation of this study may have changed due to the dynamic changes in the information and communication technology industry and how these are employed in a particular country and region of the world. Thus, results may not be generalised to other contexts. The study has a methodological limitation as it only had one informant who could respond to the study questions. Practical implications: The study provides a practical application of using the contextualism theory to analyse e-commerce entrepreneurship in SMN. Social implications: The application of e-commerce using SMNs such as Facebook widens the scope of tools that SMEs may use. Originality/value: The study provides a theoretical lens into the understanding of an e-commerce entrepreneurship process using a contextualism theory. The paper showcases how e-commerce using Facebook can be portrayed in a developing country context.